DESAIN PENGEMBANGAN BAHAN AJAR BAHASA ARAB BERBASIS MACROMEDIA FLASH DI MADRASAH IBTIDAIYAH NEGERI (MIN) PEMURUS DALAM BANJARMASIN - Ahmad Nazif (STAI AL FALAH Banjarbaru, 2020)
This research aims to find out the design of Macromedia flash-based teaching materials development in Arabic subjects for Madrasah Ibtidaiyah Negeri (MIN) Pemurus Dalam Banjarmasin and to know the response of students in the development of Macromedia flash-based teaching materials in Arabic subjects for Madrasah Ibtidaiyah Negeri (MIN) In Banjarmasin. The approach used in this study is collaborative research that combines qualitative and quantitative research approaches. The method used in this study is the Research and Development method. In the technicality of this study, researchers used the four D (4D) Model development model. The results showed that the development of Arabic language teaching materials based on Macromedia flash in Madrasah Ibtidaiyah Negeri (MIN) Pemurus Dalam Banjarmasin through the Four-D Model device development model has an excellent response in students' interest in teaching materials development products, the ability to increase motivation, tendency to create interest in learning, allow students to learn independently, and to create complacency. Keywords: Learning design, Macromedia flash.